CONCISE REVIEW ON THE FREQUENCY, MAJOR RISK FACTORS AND SURVEILLANCE OF HEPATOCELLULAR CARCINOMA (HCC) IN Β-THALASSEMIAS: PAST, PRESENT AND FUTURE PERSPECTIVES - Vincenzo De Sanctis (Mediterranean Journal of Hematology and Infectious Diseases)
Due to the recent alarming increase in the incidence of hepatocellular carcinoma (HCC) in thalassemias, the aim of the present report is to review briefly the frequency, the major risk factors and the surveillance of HCC in β-thalassemias. Over the past 33 years, 153 cases of HCC were reported in patients with thalassemia, mainly in Italy, and Greece. Among HCV-infected patients additional factors promoting development of  HCC, included: advanced age, male sex, chronic hepatitis B (CHB) coinfection, and iron overload. For early diagnosis of HCC sequential ultrasound screening  is recommended  especially for thalassemia patients with chronic hepatitis C (CHC), that coincide with (one or more) additional risk factors for HCC.  Here we report also the preliminary data of thalassemic patients, above the age of 30 years, followed in 13 different centers. The total number of enrolled patients was 1,313 (males: 612 and 701 females). The prevalence of HCC in thalassemia major patients [characterized by transfusion-dependency (TDT)] and thalassemia intermedia [characterized by nontransfusion dependency (NTDT)] was 1.68 % and 1.98 % ,respectively The lowest age at diagnosis was 36 years in TDT and 47 years in NTDT patients.We hope that our review can be used to develop more refined and prospective analyses of HCC magnitude and risk in patients with thalassemia, and to define specific international guidelines to support clinicians for an early diagnosis and treatment of HCC in thalassemic patients.